Efficacy, safety, and tolerance of the non-ergoline dopamine agonist pramipexole in the treatment of advanced Parkinson's disease: a double blind, placebo controlled, randomised, multicentre study - Pinter, M (BMJ Group, 1999)
OBJECTIVES—Pramipexole, a non-ergot dopamine D2/D3 receptor agonist, was investigated as an add on drug in advanced parkinsonian patients with motor fluctuations to assess efficacy, safety, and tolerance. METHODS—Seventy eight patients of either sex with advanced Parkinson's disease and treatment complications such as motor fluctuations were enrolled into a double blind, placebo controlled, randomised, multicentre study (phase II) and assigned to add on treatment with pramipexole (n=34) versus placebo (n=44) to a previously stabilised antiparkinsonian medication (7 week dose titration interval, 4 week maintenance period). The primary end point of efficacy was the change from baseline in the total score of the unified Parkinson's disease rating scale (UPDRS) in the on "period" (2 hours after intake of study medication). Safety and tolerability were assessed on the basis of adverse events, vital signs, laboratory measurements, and ECG recordings. RESULTS—There was a significant improvement of the pramipexole group in UPDRS total scores, subscores part II, III (activities of daily living and motor examination), and IV (complications of therapy). Mean UPDRS total score decreased by 37.3% under pramipexole compared with 12.2% under placebo (p<0.001). Patients under pramipexole reported an overall reduction in "off" periods of 12%—resulting in 1.7 more hours "on" time a day—compared with an increase in "off" periods of 2% under placebo. There were no unexpected safety results. The adverse event profile disclosed a high tolerability. The most important adverse events under pramipexole were fatigue, dyskinesia, and vivid dreams. CONCLUSION—Pramipexole administration is an efficacious and well tolerated add on therapy in patients with advanced Parkinson's disease with an improvement in activities of daily living, motor function, and treatment associated complications.